Experimental and Numerical studies on Opening and Velocity Influence on Sediment Erosion of Pelton Turbine Buckets. (August 2021) - Ge, Xinfeng; Sun, Jie; Zhou, Ye; Cai, Jianguo; Zhang, Hui; Zhang, Lei; Ding, Mingquan; Deng, Chaozhong; Binama, Maxime; Zheng, Yuan
Abstract: Sediment erosion of Pelton turbines seriously damage the economic benefits and safe operation of the power station under the high head. The gas-liquid-solid three-phase unsteady flow calculation was carried out using the Eulerian-Lagrangian method to study the influence of velocity and nozzle opening on buckets torque and erosion. Experimental research were carried out under the condition of clear water and sediment-laden flow, the experimental results are in good agreement with the numerical simulation results, which proves the reliability of the calculation model and calculation method. The conclusions obtained from the numerical simulation are as follows: after adding the sediment particles, there is a slight delay of the bucket torque curve. Compared to clear water, the maximum torque of a single bucket will increase by about 2% in sediment-laden flow under different scenarios (the particle concentration is 1%, the particle size is 0.1 mm, the velocity range is 28–32 m/s, and the nozzle opening range is 50%–100%). For particles with strong flowability, the erosion region is highly consistent with the high-pressure zone. The increase in the velocity will increase the erosion rate on buckets. The nozzle opening change has little effect on the erosion region and maximum erosion rate. Meanwhile, the number of eroded buckets is three at the same moment, which is not affected by the nozzle opening change. This paper could provide some theoretical assistance for runner manufacturing, optimization design, and maintenance. Highlights: The hydro-abrasive erosion of Pelton turbine buckets is carried out to study. The results of numerical simulation and field test are compared. The changing process of bucket torque is revealed. The relationship between pressure and erosion is explored.